Effect of antioxidant on the oxidation stability and combustion–performance–emission characteristics of a diesel engine fueled with diesel–biodiesel blend. (December 2015) - Rashedul, H.K.; Masjuki, H.H.; Kalam, M.A.; Teoh, Y.H.; How, H.G.; Rizwanul Fattah, I.M.
Highlights: Alexandrian laurel or Calophyllum inophyllum biodiesel blend fulfill the ASTMD7467 specification. Addition of antioxidant to biodiesel higher the oxidation stability. Antioxidant treated blends showed lower NOX and BSFC compared to untreated blend. Antioxidant treated blends showed higher CO, HC and smoke compared to untreated blend. Abstract: Alexandrian laurel or Calophyllum inophyllum oil is recently considered one of the most anticipated nonconsumable or nonedible biodiesel sources. An attempt has been made in this study to increase the oxidation stability and investigate the engine performance, emission, and combustion characteristics of a diesel engine by adding 1% (by vol.) of two antioxidants, such as 2, 6-Di-tert.-butyl-4-methylphenol and 2, 2′-methylenebis (4-methyl-6-tert-butylphenol), in higher percentages of C. inophyllum biodiesel (CB30) with diesel fuel (B0). The experiment was performed on a single-cylinder, water-cooled, direct-injection diesel engine for this purpose. The addition of both antioxidants increased the oxidation stability without significantly changing other physicochemical properties. Results also show that the antioxidants enhanced the start of combustion of biodiesel, which resulted in a short ignition delay. The peak pressure and the peak heat release rate during premixed combustion phase of pure CB30 and its modified blend with antioxidant were higher than those of B0. Both antioxidant blends showed higher brake power, higher brake thermal efficiency, and lower brake specific fuel consumption than pure CB30. Both antioxidants significantly reduced NOX emission; however, CO, HC, and smoke opacity were slightly higher than those of CB30. Based on this study, Alexandrian laurel or C. inophyllum biodiesel blend (CB30) with antioxidant can be used as an alternative fuel in a diesel engine without modifications.